FINANCIAL, PRICING AND TARIFF POLICY IN THE FIELD OF HOUSING AND UTILITIES: MAIN ISSUES, TRENDS AND SOLUTIONS - A. N. Ryakhovskaya (Стратегические решения и риск-менеджмент, 2014)
Reasons of low efficiency of institutional transformations in the field of housing and utilities are being studied; and specific features of public utility companies related to natural monopolies, as well as possible options of solving such issues are being considered; necessity of state regulation of their activity has been justified. Provisions to be taken into account at establishment of tariff policy in housing and utilities services have been shown.